Réseaux de villes et détermination des pressions urbaines - Fabrice Decoupigny; Sébastien Passel (Cybergeo, 2014)
Within a Network of cities, the urban growth process depends on two spatial processes at two different scales. First, urbanization grows by consuming land reserves (urban sprawl) and increasing urban density. The second depends on the extension of the network of cities induced by mobility to find open spaces to urbanize. The aim of this paper is to construct an index of urban pressure able to estimate the potential spaces of urbanization. We construct this index using spatial variables that incorporate accessibilities and land uses. The pressure index is used to assess the vulnerabilities caused by the growth of metropolitan sprawl.